The phase and microstructure changes in 45# steel irradiated by intense pulsed ion beams; Surface and Coatings Technology; Vol. 128-129, iss. 1 - Han B. X.; Yan S.; Le X. Y.; Zhao W. J.; Remnev G. E. Gennady Efimovich; Opekounov M. S.; Isakov I. F.; Grushi I. I. (2000, 2000)
Title screen